Demons of good and evil - Harrison, Kim, 1966- (Harrison, Kim, 1966- Hollows, 2023)
"Rachel Morgan will learn that the price of loyalty is blood in the next Hollows novel from #1 New York Times bestselling author Kim Harrison. Rachel Morgan, witch-born demon, suspected that protecting the paranormal citizens of Cincinnati as the demon subrosa would be trouble. But it's rapidly becoming way more trouble than even she could have imagined. While Rachel and her friends may have vanquished the trickster demon Hodin, his mysterious associate known only as "The Mage" is eager to finish what Hodin started, beginning with taking down Rachel's power structure piece by piece. When he frames Rachel for the death of a powerful coven member and the vampire leaders in DC threaten to send a new master vampire to take the city in hand, Rachel's friends Ivy and Pike are forced into hiding, and even her lover, Trent, finds himself under fire. With her world falling apart, Rachel desperately needs help. But with all of her supporters under attack, her only hope is to make a deal with the unlikeliest of allies. . . "--